Histopathological and environmental effects of the insecticide, sumithion on the fish, tilapia (Oreochromis niloticus) in pond condition (International Journal of Agricultural Research, Innovation and Technology, 2019)
The present research work was conducted to evaluate the effects of organophosphate insecticide, sumithion on water quality parameters, density of plankton population and histological changes of kidney and liver of the fish, tilapia (Oreochromis niloticus) in aquaculture ponds during July to December 2016. The experiment was conducted with four treatments, each with two replications. Treatment T0 was used as control (no sumithion) and other three treatments with 0.025 ppm (T1), 0.050 ppm (T2) and 0.100 ppm sumithion (T3). The water quality parameters such as dissolved oxygen, free carbon dioxide, pH, total alkalinity, NO3-N and PO4-P fluctuated significantly under four treatments during the experimental period but they were not affected by sumithion application. The phytoplankton densities (×105 cells L-1) was not affected by sumithion. Six genera of phytoplankton populations were found in the experimental ponds. On the other hand, zooplankton population densities (×103 cells L-1) were significantly reduced with increasing doses of sumithion (T2 and T3) in comparison with that of control (T0). Histological changes of kidney were observed after application of sumithion. The renal corpuscle, collecting duct, hematopoietic cells and other cells of the kidney in control (T0) were normal and systematically arranged. Abnormal collecting duct, Intra-cellular space, degenerated renal corpuscle, irregular shaped blood vessel, ruptured membrane large vacuole and necrosis were found in T1, T2 and T3.Normal structure of liver cells such as hepato-pancreas, hepatic cell and blood vessel were observed in T0 (control). Sumithion exposed liver sections showed rupturedhepato-pancreas, necrosis, hemorrhage, intra-cellular space, degenerated hepatopancreas and large vacuole were found in T1, T2 and T3. Therefore, it reveals that sumithion has adverse effects on kidney and liver of the test fish. So, sumithion should not be used indiscriminately in agriculture and aquaculture practices. It may be concluded from the research finding that dissolved oxygen, free carbon dioxide, pH, total alkalinity, PO4-P, NO3-N, phytoplankton and zooplankton values under treatment, T0, are significantly different from treatments T1, T2, and T3 in most cases.Int. J. Agril. Res. Innov. & Tech. 9 (1): 84-95, June, 2019